Effect of taxifolin on development of retinopathy in alloxan-induced diabetic rats. (3rd July 2019) - Ahiskali, Ibrahim; Pinar, Can Lokman; Kiki, Murat; Mammadov, Renad; Ozbek Bilgin, Asli; Hacimuftuoglu, Ahmet; Cankaya, Murat; Keskin Cimen, Ferda; Altuner, Durdu
Abstract: Purpose: Diabetic retinopathy (DR) is one of the leading causes of blindness. In DR patients, antioxidant defence is disrupted, and production of reactive oxygen species and pro-inflammatory cytokines such as interleukin 1β (IL-1β) and tumour necrosis factor alpha (TNF-α) increases. Taxifolin has been reported to suppress reactive oxygen species, IL-1β and TNF-α production. The aim of this study is to biochemically and histopathologically examine the protective effect of taxifolin against DR damage induced by alloxan. Materials and methods: Alloxan received rats with a blood glucose level of ≥250 mg/dL were divided into taxifolin-treated (TAX) ( n  = 6), diabetic control (DC) ( n  = 6) groups. There were rats received only saline in non-diabetic control (NC) group ( n  = 6). Taxifolin (50 mg/kg) was orally administered to the TAX group rats. DC and NC rats received the same volume of saline as a solvent. This procedure was repeated once a day for 3 months. At the end of this period, animals were killed by high dose thiopental sodium anaesthesia. Histopathological examinations were then performed on excised rat eyes. Malondialdehyde (MDA), total glutathione (tGSH), IL-1β and TNF-α levels were measured in obtained blood samples. Results: MDA, IL-1β and TNF-α levels were significantly increased in blood samples of DC group rats with hyperglycemia induced by alloxan compared with NC group ( p  < 0.0001), and decreased in the TAX group compared with the DC group ( p  < 0.0001). The levels of tGSH were significantly decreased in blood samples of DC group rats compared with NC group ( p  < 0.0001), and increased in the TAX group compared with the DC group ( p  < 0.0001). Histopathologically, retinal ganglion cells of the TAX group had a slightly dilated and congested blood vessel, and severe damage was inflicted to the retinal ganglion cell layer of the DC group. Conclusions: Experimental results suggest that taxifolin may be beneficial in the treatment of DR.